Modulation of the nociceptive withdrawal reflex in walking is not changed by the presence of tonic pain - Joanna Reeves; Connor Thacker; Geoffrey Cunningham; Sam Hughes; Jennifer L. Davies (Experimental Brain Research, 2026)
Tonic pain inhibits the nociceptive withdrawal reflex (NWR). NWR magnitude varies across the gait cycle, but it is unknown whether tonic pain affects this phase-dependent modulation of the NWR during walking. Sixteen healthy participants (mean ± SD age: 29 ± 9 years, 3 males) walked on a treadmill with and without tonic pain applied to the left arm. Lower-limb kinematics and electromyography (EMG) from bilateral biceps femoris, vastus lateralis, soleus and tibialis anterior were recorded. At predefined points in the gait cycle, a brief electrical stimulus was applied to the arch of the right foot to elicit an NWR. Reflex responses were calculated from the EMG as a percentage difference to the EMG present without any stimulation. There was a significant effect of gait phase on reflex response in all muscles except ipsilateral biceps femoris. When accounting for the intensity of tonic pain, there was a 0.64 decrease in normalised reflex response in the contralateral tibialis anterior with tonic pain versus control ( p = 0.009). There were no other effects of tonic pain on reflex response ( p > 0.05). There was an increase in knee flexion on the stimulated leg when it was unloading, however there was large variability in the kinematics. Stimulation during loading response saw around a 3° increase ( p = 0.007) in dorsiflexion in the contralateral leg. Our findings suggest that tonic pain does not influence the modulation of the NWR during walking. We propose that the need to maintain balance overrides any effects of endogenous pain modulation.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A perspective on green, blue, and grey spaces, biodiversity, microbiota, and human health - John D. Potter; Collin Brooks; Geoffrey Donovan; Chris Cunningham; Jeroen Douwes (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Degrees of change: between and within population variation in thermal reaction norms of phenology in a viviparous lizard - George D. Cunningham; Geoffrey M. While; Mats Olsson; Gabriella Ljungström; Erik Wapstra (Ecology, 2020)
As the earth warms, populations will be faced with novel environments to which they may not be adapted. In the short term, populations can be buffered against the negative effects, or maximize the beneficial effects, of such environmental change via phenotypic plasticity and, in the longer term, via adaptive evolution. However, the extent and direction of these population‐level responses will be dependent on the degree to which responses vary among the individuals within them (i.e., within population variation in plasticity), which is, itself, likely to vary among populations. Despite this, we have estimates of among‐individual variation in plastic responses across multiple populations for only a few systems. This lack of data limits our ability to predict the consequences of environmental change for population and species persistence accurately. Here, we utilized a 16‐yr data set from climatically distinct populations of the viviparous skink Niveoscincus ocellatus tracking over 1,200 litters from more than 600 females from each population to examine inter‐ and intrapopulation variability in the response of parturition date to environmental temperature. We found that these populations share a common population‐mean reaction norm but differ in the degree to which reaction norms vary among individuals. These results suggest that even where populations share a common mean‐level response, we cannot assume that they will be affected similarly by altered environmental conditions. If we are to assess how changing climates will impact species and populations accurately, we require estimates of how plastic responses vary both among and within populations.

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)